2015
DOI: 10.1208/s12249-015-0432-8
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aspirin Crystals Generated by a Modified Vapor Diffusion Method

Abstract: Abstract. The objectives of the current investigation were (1) to study the influence of selected two different non-solvents (diethylether and dichloromethane) on the drug crystal formation of a model drug, aspirin (ASP-I) by the modified vapor diffusion method and (2) to characterize and compare the generated crystals (ASP-II and ASP-III) using different analytical techniques with that of unprocessed ASP-I. When compared to the classical vapor diffusion method which consumes about 15 days to generate drug cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It has been reported that the significant difference in the enthalpy could be due to changes in the crystallinity of acetylsalicylic acid after the solubility test. This has been shown when acetylsalicylic acid has been crystallized from various organic solvents ( 53 ). The enthalpy data in Table II shows that the acetylsalicylic acid crystals filtered after the solubility test in 100% water have less crystallinity compared to untreated acetylsalicylic acid.…”
Section: Resultsmentioning
confidence: 78%
“…It has been reported that the significant difference in the enthalpy could be due to changes in the crystallinity of acetylsalicylic acid after the solubility test. This has been shown when acetylsalicylic acid has been crystallized from various organic solvents ( 53 ). The enthalpy data in Table II shows that the acetylsalicylic acid crystals filtered after the solubility test in 100% water have less crystallinity compared to untreated acetylsalicylic acid.…”
Section: Resultsmentioning
confidence: 78%
“…Such increased activity of the metal complexes can be explained on the basis of Overtone concept and Tweedy chelation theory. 56,57) According to the overtone concept of cell permeability, the lipid membrane that surrounds the cell favors the passage of only lipid-soluble materials; therefore, lipophilicity is an important factor which controls the antibacterial activity. On chelation, polarity of the metal ion is reduced to a greater extent due to the overlapping of ligand orbital and partial sharing of the positive charge of the metal ion with donor groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when the molecules on the crystal plane are peeled off by cleavage, the number of stacked crystal planes and the peak intensity are reduced. 29) It is also shown that the XRD peak of the ground sample is lower than that of the unground sample. In other words, it is reported that the peak area of PXRD is reduced when the number of stuck crystal facets is reduced by grinding.…”
Section: Prediction and Evaluation Of Changes In The Surface Physical Propertiesmentioning
confidence: 96%
“…In other words, it is reported that the peak area of PXRD is reduced when the number of stuck crystal facets is reduced by grinding. 29) The (1 0 0) and (0 0 2) peak of PXRD were integrated and the peak areas were obtained. Moreover, the total integrated value of each PXRD was calculated.…”
Section: Prediction and Evaluation Of Changes In The Surface Physical Propertiesmentioning
confidence: 99%